Neuroimaging predictors of malignant brain oedema after thrombectomy in ischemic stroke: a systematic review and meta-analysis - Linrui Huang; Xindi Song; Jingjing Li; Yanan Wang; Xing Hua; Meng Liu; Ming Liu; Simiao Wu (Annals of Medicine)
Background We systematically reviewed neuroimaging predictors for malignant brain oedema (MBE) after thrombectomy in patients with ischemic stroke.Methods We searched MEDLINE and EMBASE in November 2023 for studies of patients with ischemic stroke. We included studies investigating neuroimaging predictors or prediction models for MBE after thrombectomy. We estimated effect size for the association between predictors and MBE by odds ratios (ORs) or standardized mean differences (SMDs), and pooled results using random-effects modelling.Results We included 19 studies (n = 6007) with 17 neuroimaging factors and 5 models. Lower Alberta Stroke Program Early CT scores (ASPECTS, n = 3052, SMD −1.84, 95% CI −2.52 – −1.16; df = 9) and longer extent of arterial occlusion at baseline were associated with higher risk of MBE. Post-thrombectomy ASPECTS was associated with MBE in general stroke patients (n = 453, SMD −2.91, −4.02 – −1.79; df = 1), but not in successfully reperfused patients (n = 110, SMD 0.24, −0.16 – 0.65). Successful reperfusion reduced risk of MBE (n = 4851, OR 0.39, 0.30–0.51; df = 13). Contrast enhancement on CT after thrombectomy was associated with higher risk of MBE (n = 998, OR 4.82, 2.53–9.20; df = 4). More reserved brain volume capacity (baseline: n = 683, OR 0.83, 0.77–0.91, p < .001; post-thrombectomy: n = 329, OR 0.53, 0.37–0.77, p < .001) and good collaterals (baseline: n = 2301, OR 0.14, 0.10–0.20, df = 3; post-thrombectomy: n = 1006, OR 0.28, 0.15–0.51; df = 2) were associated with lower risk of MBE.Conclusion Lower ASPECTS and longer arterial occlusion at baseline, and post-thrombectomy CT contrast enhancement increased risk of MBE. Reperfusion after thrombectomy, more reserved brain volume and good collaterals at baseline and post-thrombectomy reduced its risk.